Efeito do suco de beterraba na magnitude e duração da resposta pressórica pós-exercicio em mulheres hipertensas - Anjos, Carla Nunes dos (2023)
In recent years, beetroot has gained notoriety for its ability to promote blood pressure reduction in the first hours after ingestion, a temporal behavior similar to post-exercise hypotension. In this context, the general objective of this study was to evaluate the effect of ingestion of beetroot juice after an exercise session on the magnitude and duration of the pressure response in hypertensive women. This is a clinical, randomized, controlled, double-blind and crossover study, carried out with 14 hypertensive women aged 40 to 60 years, who participated in three procedures: 1) ingestion of beetroot juice 2 hours after exercise (SBE), 2) ingestion of fruit drink 2 hours after exercise (RFE) and 3) control without exercise and drink (CON). An anthropometric assessment was performed on the participants first visit to the laboratory. Clinical blood pressure was measured before, immediately after exercise and every 10 minutes during the post-exercise recovery period or rest. Ambulatory blood pressure was measured using ambulatory blood pressure monitoring. Nitrite, total antioxidant capacity and malondialdehyde analyzes were performed. Two-way ANOVA for repeated measures was performed to verify differences between protocols. A significance level of p<0.05 was adopted. As participants were overweight, in addition to the influence of high waist. Beetroot juice significantly increased plasma nitrite concentrations between baseline and 2 hours after ingestion of the juice (33.4 ± 32.5 μM to 47.0 ± 36.0 μM; p=0.013). Both SBE and RFE procedures promoted hypotension in clinical monitoring at 60 minutes post-exercise, with a reduction in systolic pressure from 10 minutes post-exercise (p<0.05), while diastolic pressure occurred at 20 minutes (p<0 .05) in relation to rest (interaction time), but with no difference between the two protocols with exercise (p>0.05). Significant reductions in ambulatory systolic pressure were observed for 17 hours post-exercise and 16 hours in diastolic pressure in SBE, while in RFE this hypotension was only noticed between 6 and 15 hours for systolic and 13 and 16 hours for diastolic compared to rest (p<0.05). Beetroot juice maintained lower blood pressure compared to the pre-exercise condition for a longer time, however, in the time x procedure interaction analysis, no significant differences were observed between the three procedures (p>0.05). No significant differences were observed in total antioxidant capacity and malondialdehyde after ingestion of beverages in the SBE and RFE procedures (p>0.05). Thus, this study confirms previous data that an exercise session promotes post-exercise hypotension, but the association with beetroot juice did not improve this pressure response, however, it showed a consistent effect by maintaining pressure reductions for a longer time than the procedure with fruit drink. fruit. On the other hand, beetroot did not improve the magnitude of post-exercise hypotension.